Transformasi Pembelajaran Vokasi Pertanian melalui Integrasi IoT dan Computer Vision pada Smart Greenhouse di SMKN 4 Barru: Penelitian - Marwan Ramdhany Edy; Muh. Ihsan Zulfikar; Nurfauziah; Putri Nirmala; Nurrahmah Agusnaya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The digital agricultural transformation demands strengthening technological literacy and skills in vocational schools, particularly in the utilization of the Internet of Things (IoT) and Computer Vision to support precision farming practices. This community service program aims to improve the competency of teachers and students of SMKN 4 Barru in integrating IoT-based Smart Greenhouse technology and Computer Vision into agribusiness learning. The activity uses a Participatory Action Research (PAR) approach through the stages of preparation, training, technology implementation, mentoring-evaluation, and sustainability, involving teachers, education staff, and students. Evaluation was conducted through pre-post tests, observation, and participatory reflection. The results showed a significant increase in participants' conceptual understanding and practical skills, including the use of temperature, humidity, and soil pH sensors for IoT-based hydroponic systems, as well as the use of Computer Vision to visually detect plant conditions. Participants also reported increased confidence in operating modern agricultural technology devices and awareness of the importance of digital-based innovation in vocational learning. Key challenges identified include the integration of sensor data into monitoring systems and the development of Computer Vision algorithms, requiring further mentoring and infrastructure strengthening. Overall, this program contributes to increasing digital literacy, readiness for the implementation of precision agriculture, and the development of a creative agro-education ecosystem relevant to the demands of Industry 4.0 in Barru Regency.